The Beholder’s Hurt Feeling - Claudia Keller (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This contribution discusses the implications of Weimar Classicism and its modern consciousness of the hermeneutical difference between antiquity and present on the perception and the methods of restoration. On the basis of Johann Heinrich Meyer’s and Johann Wolfgang Goethe’s experiences with modern restoration in Italy it is shown how a critique of previous restorations leads to a new sensibility in dealing with artworks and as a consequence to an aesthetic of the fragment.